Pengaruh Motivasi dan Lingkungan Kerja terhadap Kinerja Pegawai pada Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Pemerintahan Kota Depok - Rayhan Febrianto; Ratnawaty Marginingsih; Wiwit Rohaeni Yulianti (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2025)
This study aims to determine the influence of motivation and work environment on employee performance at the Investment and One-Stop Integrated Services Office of the Depok City Government. The background of this research is based on the importance of human resources in supporting organizational success, as well as the identified issues such as lack of work discipline and suboptimal work environment conditions at DPMPTSP Depok. This research employs a quantitative approach with data collected using a Likert scale-based questionnaire. The sample consisted of 59 respondents selected using a saturated sampling technique. The results show that motivation has a positive and significant effect on employee performance, with a t- value of 4.317 > t-table 2.002 and a significance level of 0.002 < 0.05. The work environment also has a positive and significant effect on employee performance, with a t-value of 6.718 > t-table 2.002 and a significance level of 0.001 < 0.05. Simultaneously, both variables significantly influence employee performance, as indicated by an F-value of 52.743 > F-table 3.16 and a significance level of 0.001 < 0.05. The coefficient of determination (R²) is 0.653, indicating that 65.3% of the variation in employee performance is explained by motivation and work environment, while the remaining 34.7% is influenced by other factors not examined in this study.